Analysis of the impact of the use of clickbait on the Twitter profiles of the Spanish media - Flores-Vivar, Jesús Miguel (2023)
The article addresses the use of clickbait in the current media ecosystem, dominated by the hegemony of social networks and in which the competition to attract the attention of users is increasing among the media. In this scenario, one of the challenges that journalism faces is misinformation, but also the challenge of attracting readers to their websites, which is why the use of headlines that seek to attract attention is becoming more and more common. of the user to click on the link, regardless of their informative rigor, which may cause further misinformation. Due to this, this work seeks to analyze the content (messages) that appear in the Twitter profiles of the main Spanish media that use techniques such as clickbait and to evaluate whether the bait headlines produce more misinformation or not, in the current panorama. Spanish media. The methodology is based on the content analysis of the Twitter profiles of Spanish media such as ABC, El País, El Mundo, Público, Diario.es, RTVE Noticias, COPE, Cadena Ser, Onda Cero, Antena 3 Noticias, Noticias Cuatro and La Sexta Noticias. The results indicate that the media analyzed make very little use of this practice and it is mainly concentrated in sections such as Society or Science. It should be noted that, despite making low use of clickbait, the use of other formulas is observed, such as questions in headlines, seeking to attract users and increase the number of page views.